STUDI KUALITAS MIKROBIOLOGI AIR SUMUR GALI SEBELUM DAN SESUDAH MENGGUNAKAN CHLORINE DIFFUSER DI DESA SELABAYA KECAMATAN KALIMANAH KABUPATEN PURBALINGGA TAHUN 2018 - Inayatus Sholikhah; Yulianto Yulianto (Poltekkes Kemenkes Semarang, 2019)
Well water dug from ground water often causes problems. Problems arise that is often found that the quality of groundwater used by the community is less qualified even in some places not worth to be consumed. For example ground water that smells, tastes, colored, turbid, contains iron (Fe) and Coliform (BPPT, 2010). The purpose of this research is to know the number of Coliform in digging well water, and to know the condition of sanitation of dug wells. The type of research used is descriptive research that aims to determine whether or not changes in dug well water after installation of chlorine diffuser in Selabaya Village Kalimanah District Purbalingga District in 2018. The results showed that the number of Coliform in dug well water still exist which is not in accordance with the applicable standards, after installed chlorine diffuser there are 3 dug wells are fixed, and there are 5 wells dug the water quality to be better. The results showed that the number of Coliform in dug well water still exist which is not in accordance with the applicable standards, after installed chlorine diffuser there are 3 dug wells are fixed, and there are 5 wells dug the water quality to be better. The conclusion that the quality of microbiology in Selabaya Village, Kalimanah District, Purbalingga Regency is obtained after the installation of chlorine diffuser water quality there is a better and there are still recommended to the community in order to use chlorine diffuser to disinfect well water dig.